Pharmacokinetics of Novel Plant Cell-Expressed Taliglucerase Alfa in Adult and Pediatric Patients with Gaucher Disease - Abbas, Richat (PLoS One, 2015)
Taliglucerase alfa is a beta-glucocerebrosidase enzyme replacement therapy approved in the United States, Israel, and other countries for treatment of Type 1 Gaucher disease in adults, and is the first approved plant cell—expressed recombinant protein. In this report, taliglucerase alfa pharmacokinetics were assessed in adult and pediatric patients with Gaucher disease from separate multicenter trials of 30 Units/kg and 60 Units/kg doses infused every 2 weeks. Serial blood samples were obtained from adult patients following single-dose administration on day 1 (n = 26) and multiple doses at week 38 (n = 29), and from pediatric patients following administration of multiple doses of taliglucerase alfa for 10–27 months (n = 10). In both adult and pediatric patients, maximum plasma concentration (C(max)), area under the plasma concentration-time curve from time zero to last measureable concentration (AUC(0-t)), and from time zero to infinity (AUC(0-∞)) were higher after 60 Units/kg dose than 30 Units/kg dose. No tendency for accumulation or change in taliglucerase alfa pharmacokinetic parameters over time from day 1 to week 38 was observed with repeated doses of 30 or 60 Units/kg in adults. After multiple doses, mean (range) dose-normalized pharmacokinetic parameters were similar for adult versus pediatric patients receiving 60 Units/kg: C(max) expressed in ng/mL/mg was 42.4 (14.5–95.4) in adults and 46.6 (34.4–68.4) in pediatric patients, AUC(0 t) expressed in ng•h/mL/mg was 63.4 (26.3–156) in adults and 63.9 (39.8–85.1) in pediatric patients, t(1/2) expressed in minutes was 34.8 (11.3–104) in adults and 31.5 (18.0–42.9) in pediatric patients and total body clearance expressed in L/h was 19.9 (6.25–37.9) in adults and 17.0 (11.7–24.9) in pediatric patients. These pharmacokinetic data extend the findings of taliglucerase alfa in adult and pediatric patients. TRIAL REGISTRATION: ClinicalTrials.gov. NCT00376168 (in adults); NCT01411228 (in children)